Ressentiment in Egalitarian Movements: Slavoj Žižek’s Response to Peter Sloterdijk - Andrijauskas, Jokūbas (Problemos, 2021)
I discuss Peter Sloterdijk’s critique of egalitarian projects presented in his book Zorn und Zeit and Slavoj Žižek’s response to it. My claim is that both of these thinkers show an oscillation between polemical and analytical aspects when using the concept of ressentiment. By using the concept of ressentiment, Sloterdijk explains the transformation of anger in Western societies. He holds that the atemporal anger, which characterized ancient greeks assumes a temporal form and becomes the project of revenge and ressentiment under Christianity and later emancipatory movements. I show that alongside this view, the author implies a political-polemical argumentation with the intent of delegitimizing the political left movements. Then I discuss the notion of ressentiment in Žižek’s view, which implies the same ambivalence, on the one hand, this concept is introduced as an alternative to Sloterdijk’s attempts at delegitimization, on the other, it seeks to explain anger and revenge related phenomena. At last, I claim that Sloterdijk’s and Žižek’s positions differ on the polemical aspect, but are compatible analytically.